Trend and Stability Analysis of Crop Production Efficiency over Western Rajasthan - Ramakrishna, G V.S; Malhotra, S P; Yadav, M D (Annals of Arid Zone, 2016)
The crop production efficiency in the districts of western Rajasthan did not improve over the last 25 years except Ganganagar district. Districts with high rainfall are more efficient and stable in crop production indicating that the farmers in the districts with low rainfall are at greater uncertainty.